Problem-based learning: Making caricature as teaching material based on folklore "Sang Piatu" for Indonesian language learning - Muktadir, Abdul; Susanti, Atika; Darmansyah, Ady; Febrina, Wulan; Irmayanti, Meiselina (LITERA, 2024)
Understanding the materials and keeping motivated are challenges for elementary students in learning the Indonesian language. It happened due to a lack of learning resources. Previous studies mentioned that local learning resources can stimulate students' comprehension, specially forming colorful visualization. Therefore, the present research observes how to develop teaching material of caricatures adopted from the folklore "Sang Piatu," by employing problem-based learning (PBL). The current research aims to boost students' interest in learning, improve students' material comprehension of Indonesian language learning, and foster cultural awareness. The research method employed is Research and Development using the ADDIE model. This research contributes significantly to developing Indonesian language teaching materials at the elementary school level. The result demonstrates the approach's effectiveness in stimulating learning interest and improving students' understanding of the material, including increasing cultural awareness. Future studies could explore the potential of other folk stories from Indonesia. The upcoming studies could also integrate application technology to enhance student engagement in the era of Society 5.0.